Contribuições da psicologia ambiental para a atenção a migrantes Involuntários: uma revisão de literatura selecionada - Liesegang, Helena Nunes de Araujo (2024)
Involuntary displacement is a phenomenon that has always existed, either due to wars, climate disasters, economic conditions or political persecution. It is, however, more eminent today, with a growing number of refugees and involuntarily displaced people each year. It is worth examining how science has articulated this phenomenon throughout its development. This work is tied to the institutional project CNPq “Subjectivities and the promotion of mental health: a sustainable development in contemporary clinical psychology,” which aims at analyzing possibilities of subjective support facing contemporary challenges and identifying theoretical and methodological contributions from different fields of clinical psychology, in accordance with UN’s Objectives of Sustainable Development. The purpose of this subproject is to describe and analyze the academic work on involuntary displacement throughout the history of some of the most important international scientific journals in Environmental Psychology: Journal of Environmental Psychology, Environment and Behavior and the Inter American Psychology Magazine. These journals were selected because of the crucial role they played in the creation and consolidation of Environmental Psychology as a field. This work contains a review of all publications from these three journals since their beginning, while searching for texts about involuntary migration, which resulted in the analysis of 19 articles. This analysis has shown that Environmental Psychology currently relies on a powerful repertoire of theoretical concepts in treating the subject, while being dormant until the 2000s. However, there has been a revival movement since the second half of the 2010s, which shows that Environmental Psychology is committed to the subject, having a promising future. hroughout this process, the research population has gradually shifted, with an initial emphasis on involuntary migrants, opening up space for research on involuntarily displaced people and refugees.This research was made possible by the financial support of Conselho Nacional de desenvolvimento Científico e Tecnológico (CNPq), Chamada CNPq no. 07/2022, processo no. 403707/2022-6